Fractional-Order Surge Control of Active Magnetic Bearings Suspended Compressor - Parinya Anantachaisilp; Zongli Lin (Actuators, 2020)
<semantics>H∞</semantics> surge control in centrifugal compressors by using active magnetic bearings (AMBs) has been successfully designed and implemented. However, the structure and design process of <semantics>H∞</semantics> surge control are quite complex. This paper reports on the design and implementation of fractional-order proportional-derivative control (FOPD) that results in the required specifications of surge control with a simple controller structure. To validate its effectiveness, the proposed FOPD surge controller has been implemented on a centrifugal compressor test rig equipped with AMBs. Simulation and experimental results show that the FOPD surge controller outperforms integer-order PD (IOPD) control in extending the surge limit in terms of the mass flow and provides similar performance as the <semantics>H∞</semantics> controller.